Association of CT-Based Delta Radiomics Biomarker With Progression-Free Survival in Patients With Colorectal Liver Metastases Undergo Chemotherapy - Ye, Shuai; Han, Yu; Pan, XiMin; Niu, KeXin; Liao, YuTing; Meng, XiaoChun (Frontiers in Oncology, 2022)
Predicting the prognosis of patients in advance is conducive to providing personalized treatment for patients. Our aim was to predict the therapeutic efficacy and progression free survival (PFS) of patients with liver metastasis of colorectal cancer according to the changes of computed tomography (CT) radiomics before and after neoadjuvant chemotherapy.